2017
DOI: 10.1515/jbcpp-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dry eye disease and its association with dyslipidemia

Abstract: Based on the findings, we emphasize that there is a strong relationship between dyslipidemia and the progression of DED particularly in women. Ophthalmologists may increase their role to educate themselves to diagnose dyslipidemia and ensure comprehensive eye care to prevent blindness and cardiovascular disease. Recent treatment modalities could be aimed to improve the quality of life of women and elderly patients suffering from DED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…In the current study, there was a significant association between DED and DM2 ( P =0.003) as well as DED and DM1 ( P =0.003), which corresponds with earlier studies for DM217,30,31 and for DM1 16. Of particular interest was our finding that there was a higher DED prevalence in those with DM2 (56% by OSDI) than for DM1 (27%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, there was a significant association between DED and DM2 ( P =0.003) as well as DED and DM1 ( P =0.003), which corresponds with earlier studies for DM217,30,31 and for DM1 16. Of particular interest was our finding that there was a higher DED prevalence in those with DM2 (56% by OSDI) than for DM1 (27%).…”
Section: Discussionsupporting
confidence: 92%
“…Of particular interest was our finding that there was a higher DED prevalence in those with DM2 (56% by OSDI) than for DM1 (27%). In our study, the prevalence of DM2-associated DED was comparable to other reports on DM2 cohorts, such as Manaviat et al30 (54.3%; determined by tear break-up time [TBUT] and Schirmer test) and Rathnakumar et al31 (53%, TBUT and Schirmer test), but was higher than that reported by Najafi et al4,32 (27.7%, as determined by tear osmolarity). This difference between our findings and Najafi et al4 might be due to the fact that in long-standing diabetes, patients with higher tear osmolarity often experience fewer dry eye symptoms 3.…”
Section: Discussionsupporting
confidence: 88%
“…HDL has been associated with increased levels of anti-inflammatory cytokines such as interleukin 10 (IL-10), that reduce production of pro-inflammatory agents such as IL-6 and tumor necrosis factor receptors, thereby inhibiting cell growth and proliferation as well as promoting apoptosis 2527. In addition, HDL levels are closely related to age-related macular degeneration (AMD),3032 dry eye (DE),33,34 and cardiovascular disease (CVD) 35. And some reports have suggested that high HDL levels are associated with an increased risk of AMD3032 whereas low HDL levels are relevant to DE and CVD 3335.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HDL levels are closely related to age-related macular degeneration (AMD),3032 dry eye (DE),33,34 and cardiovascular disease (CVD) 35. And some reports have suggested that high HDL levels are associated with an increased risk of AMD3032 whereas low HDL levels are relevant to DE and CVD 3335. In our study, the CRC patients with ocular metastases had increased serum levels of HDL, which is opposite to the correlation between HDL and the incidence of CRC, but in line with the changes in some ocular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) can cause many ocular complications such as keratoconjunctivitis, retinopathy, dry eye disease (DED), cataract, nerve palsies, glaucoma and macular edema. In recent years, in addition to diabetic retinopathy has received widespread attention for its role in causing blindness, the dry eye problem also has generated attention for its high incidence in diabetics [1,2].…”
Section: Introductionmentioning
confidence: 99%